Rainfall Distribution in the Srepok River Basin (Vietnam) - Phan, Thi Thanh Hang; Do, Thi Van Huong; Nguyen, Thi Bich; Dang, Hoa Vinh; Ngo, Tra Mai; Pham, Thi Bich Thuc (Ukrainian Geographical Journal, 2025)
Srepok is an international river basin in the Central Highlands in Vietnam with an area of about 18,230 km2, and is divided into ten irrigation sub-basins. This study applies the statistical method to assess the distribution of rainfall in the past using observed data (1981–2020) and the downscaling method to predict for the periods 2021–2040, 2041–2060, 2061–2080, and 2081–2100 under the medium and high emission scenarios (SSP2-4.5 and SSP3-7.0). Based on observed data, the annual rainfall in 1981–2020 decreased gradually from the North and South to the center and decreased from the West to the East of the basin. Rainfall (May to October) in the rainy season reached 1,494 mm, accounting for 84.4% of annual rainfall. Under both SSP2-4.5 and SSP3-7.0 scenarios, the annual rainfall in the basin and the irrigation sub-basins tends to decrease. The low rainfall area tends to expand every 2 decades to the end of the 21st century. The rainfall amounts remain constant during the dry season but tend to decrease in the rainy season. The rainfall tends to increase from the East to the West of the basin in the rainy season and from the North to the South in the dry season. However, monthly and annual rainfall between periods is relatively stable under the SSP2-4.5 scenario.
Keywords: rainfall; distribution; Srepok river basin; CMIP6